The sufficient descent condition of nonlinear conjugate gradient method - Basri, Sri Mazzura; Mamat, Mustafa; Ghazali, Puspa Liza (Science Publishing Corporation, 2018)
Non-linear conjugate gradient methods has been widely used instrumental in solving large scale optimization. These methods has been proved that only required very low memory other than its numerical efficiency. Thus, many studies have been conducted to improve these methods to find the most efficient method. In this paper, we proposed a new non-linear conjugate gradient coefficient that guarantees sufficient descent condition. Numerical tests indicate that the proposed coefficient is better than the three classical conjugate gradient coefficients.